The Impact of Income on academic staff Job Satisfaction at Public research Universities, Malaysia - Mehrad, Aida (Universitas Ahmad Dahlan, 2014)
AbstractThe presence of job satisfaction as a vital factor amongst academic staff in university is too considerable. Furthermore, recognizing principal factors that influence on job satisfaction assumed much significant, because of these factors appear various normal and abnormal behavior at workplace. In this case, the present study focused on income as external factor that impacts on job satisfaction and examines the association between these two factors among academic staffs at public universities in Malaysia. The sample of the study was 440 academic staff that worked in public universities and completed the job descriptive index inventory. Additionally, the result showed there is significant relationship between income and the amount of job satisfaction that analyzed by ANOVA test. As well, the existing paper supports the effect of income on job satisfaction among academic staff.Key word: Income, job satisfaction, and university academic staff